1997
DOI: 10.4319/lo.1997.42.4.0714
|View full text |Cite
|
Sign up to set email alerts
|

Use of elemental composition to predict bioavailability of dissolved organic matter in a Georgia river

Abstract: The relationship between the bioavailability of dissolved organic matter (DOM) and its bulk chemical composition was examined on three dates at 10 sites on the Ogeechee River, a blackwater river in Georgia, Samples of riverine DOM were concentrated from filtered river water using reverse osmosis. In addition, particulate organic matter (POM), in the form of leaf litter, algae, and macrophytes, was leached with synthetic rainwater to obtain fresh DOM. Elemental composition, carboxylic acid content, and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
227
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(253 citation statements)
references
References 26 publications
(12 reference statements)
22
227
3
1
Order By: Relevance
“…Accumulation of bacterial biomass (bacterial regrowth bioassays; mg bacterial biomass mg Ϫ1 initial DOC) is inversely correlated with the C : N of the bulk DOM in a number of studies. These include studies with Ogeechee River water (r 2 ϭ 0.63, n ϭ 14; one outlier omitted from regression) and with plant/algal leachate (r 2 ϭ 0.79, n ϭ 5; our calculations using data in Sun et al 1997), and across four rivers (r 2 ϭ 0.84, n ϭ 4; our calculations using data in Hopkinson et al 1998). This correlation with C : N suggests that proteinaceous moieties are preferentially consumed (Sun et al 1997).…”
Section: Bioavailability Of Don By Source and Season-mentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of bacterial biomass (bacterial regrowth bioassays; mg bacterial biomass mg Ϫ1 initial DOC) is inversely correlated with the C : N of the bulk DOM in a number of studies. These include studies with Ogeechee River water (r 2 ϭ 0.63, n ϭ 14; one outlier omitted from regression) and with plant/algal leachate (r 2 ϭ 0.79, n ϭ 5; our calculations using data in Sun et al 1997), and across four rivers (r 2 ϭ 0.84, n ϭ 4; our calculations using data in Hopkinson et al 1998). This correlation with C : N suggests that proteinaceous moieties are preferentially consumed (Sun et al 1997).…”
Section: Bioavailability Of Don By Source and Season-mentioning
confidence: 99%
“…These include studies with Ogeechee River water (r 2 ϭ 0.63, n ϭ 14; one outlier omitted from regression) and with plant/algal leachate (r 2 ϭ 0.79, n ϭ 5; our calculations using data in Sun et al 1997), and across four rivers (r 2 ϭ 0.84, n ϭ 4; our calculations using data in Hopkinson et al 1998). This correlation with C : N suggests that proteinaceous moieties are preferentially consumed (Sun et al 1997). Although we cannot directly compare our results to the above studies because of differences in methodologies, we found no statistically significant relationship between the C : N ratio of the DOM added and the proportion of DON that was bioavailable either across all sources (r 2 ϭ 0.04, P ϭ 0.12) or within a source (r 2 Յ 0.04, P Ն 0.4).…”
Section: Bioavailability Of Don By Source and Season-mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, wetland inputs of DOM to streams can have a profound impact on the chemistry (Billett et al 2006) and biology (Sun et al 1997) of aquatic ecosystems. Aquatic DOC concentrations have been shown to be signiWcantly correlated with peatland coverage (Aitkenhead et al 1999), wetland area (Gorham et al 1998) and wetland type (Xenopoulos et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DOC encompasses a large pool of molecules, which depending on their source (i.e., autochthonous versus allochthonous), can vary in chemical composition and bioavailability (e.g., Sun et al, 1997;Jaffé et al, 2012). Allochthonous constituents typically dominate the DOC pool, with the exception of alpine and arid catchments devoid of major terrestrial vegetation (e.g., Milner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%